Did sexual behaviour differences between HIV infection and treatment groups offset the preventative biological effects of ART roll-out in Zimbabwe?. (2nd September 2021) - Gregson, Simon; Nyamukapa, Constance
Abstract : Declines in HIV incidence have been slower than expected during the roll-out of antiretroviral treatment (ART) services in sub-Saharan African populations suffering generalized epidemics. Using data from a population-based, open cohort HIV sero-survey (2004–13), we found evidence for initial reductions in sexual activity and multiple sexual partnerships, followed by increases during the period of ART scale-up in areas of high HIV prevalence in Manicaland, east Zimbabwe. Recent population-level increases in condom use were also recorded, but largely reflected high use by the rapidly growing proportion of HIV-infected individuals on treatment. Sexual risk behaviour increased in susceptible uninfected individuals and in untreated (and therefore more infectious) HIV-infected men, which may have slowed the decline in HIV incidence in this area. Intensified primary HIV prevention programmes, together with strengthened risk screening, referral, and support services following HIV testing, could help to maximize the impact of 'test-and-treat' programmes in reducing new infections.